Dysfunctional kidney due to dysfunctional thyroid! - S Rashmi; A C Nirmala (Wolters Kluwer Medknow Publications, 2021)
Hypothyroidism can have various musculoskeletal manifestations such as myalgia, myopathy, or myositis. However, hypothyroidism causing rhabdomyolysis is rare. Moreover, the occurrence of acute kidney injury due to rhabdomyolysis precipitated by hypothyroidism is a rare, life-threatening yet reversible cause for renal dysfunction. Here, we report a case of an 18-year-old girl who presented with renal dysfunction following acute gastroenteritis, and on evaluation for worsening renal functions, she was found to have rhabdomyolysis due to hypothyroidism.